Commuter cycling and health. - Andersen, Bo; Cooper, Ashley R. (MetaGIS Infosysteme, 2011)
Commuter cycling may potentially improve health in the population. Commuter cyclists have lower mortality rate, and studies in children suggest that cyclists are more fit. Most studies about cycling and health are observational studies, and little has been published where the effects of interventions have been tested. The chapter highlights some of the key results from the prospective studies, and provide new data on health benefits of cycling to school. Higher physical fitness level was found in children cycling to school compared to passive travellers whereas walkers have similar fitness level as passive travellers. Cardiovascular risk factor profile is also better in cyclists, and in the most recent data a difference between cyclists and passive travellers or walkers of 1.29 SD was found in composite CVD risk factor score consisting of the sum of z-scores for systolic blood pressure, triglyceride, cholesterol:HDL ratio, HOMA score, sum of skinfolds and low fitness. The odds ration of having clustered risk was 0.49 (95% CI 0.30-0.80) in cyclist compared to passive travelers, but no protection was found for walking. (B.A.)
Keywords: Individualverkehr; Fahrradverkehr; Verkehrsmittelwahl; Mobilität; Gesundheit; Fahrradbenutzung; Mobilitätsverhalten; Gesundheitsförderung; Fahrradnutzung; Arbeitsweg; Gesundheitsrisiko; Berufsverkehr